Reforming Social Justice in Neoliberal Times - Brodie, Janine M (Studies in Social Justice, Vol 1, Iss 2, Pp 93-107 (2007), 2007)
This article unfolds in three stages. First, it locates the emergence of modern conceptions of social justice in industrializing Europe, and especially in the discovery of the “social,” which provided a particular idiom for the liberal democratic politics for most of the twentieth century. Second, the article links this particular conception of the social to the political rationalities of the postwar welfare state and the identity of the social citizen. Finally, the article discusses the myriad ways in which this legacy of the social and social justice has been disrupted, although not yet fully displaced, by the economic orthodoxies and individualization that inform the contemporary neoliberal governing project in Canada. The result, the article concludes, has been the institutionalization of insecurity, which demands the renewal of a social way of seeing and a politics of social justice on local and global scales.
Political Science
Keywords: criminology; neoliberalism; political economy; social and public welfare; social governance; social justice; social pathology; social policy; social sciences; sociology